(untitled) (Scientific journal of the Fergana State University, 2024)
The article talks about the importance of improving the professional and pedagogical skills of students of music education and professional knowledge, which is one of its branches. Today, the activities emphasize the effectiveness of the music teacher, preparation for the start of teaching activity, and, first of all, the importance of pedagogical skill, mastery of the types of competencies necessary in each pedagogical process. The cognitive competence of music education students in the process of conducting music education lies in the fact that students regularly update their professional knowledge, gradually develop skills and subsequently teach as music teachers and solve problems independently. thinking, it is proposed to improve his cognitive psychology using effective methods of the pedagogical approach.